2018
DOI: 10.26565/2313-6693-2018-36-05
|View full text |Cite
|
Sign up to set email alerts
|

Condition of Lipid Peroxide Oxidation and Antioxidant System in Patients With Infectious Mononucleosis

Abstract: The indicators of the activity of lipid peroxidation and the antioxidant system were studied in dynamics in 158 patients with infectious mononucleosis depending on the severity of the clinical course of the disease. It is proved that lipid peroxidation is significantly activated in patients with infectious mononucleosis as the severity of the disease increases and therefore increases the oxidative activity of blood plasma, the concentration of dyne conjugates and malondialdehyde in the blood, decreases the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The data above indicated that chickenpox patients with moderate and severe course of the disease developed a pronounced imbalance between the state of the oxidative and antioxidant systems, which was accompanied by an increase in the free radical oxidation of fatty acids and the accumulation of toxic DC and MDA increased concentration [7,13]. A marked deficiency of glutathione, which normally inactivates free radicals [14], also developed and could have a negative impact on the course of the disease and its complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data above indicated that chickenpox patients with moderate and severe course of the disease developed a pronounced imbalance between the state of the oxidative and antioxidant systems, which was accompanied by an increase in the free radical oxidation of fatty acids and the accumulation of toxic DC and MDA increased concentration [7,13]. A marked deficiency of glutathione, which normally inactivates free radicals [14], also developed and could have a negative impact on the course of the disease and its complications.…”
Section: Resultsmentioning
confidence: 99%
“…It accumulates in tissues in patients with moderate to severe chickenpox as a result of a decrease in glutathione reductase activity. Oxidized glutathione inactivates membrane adenosine triphosphatase, hexokinase, glucose-6-dehydrogenase, inhibits phosphorylation and nuclear RNA synthesis, and inhibits protein synthesis due to the formation of protein-thiol-glutathione crosslinks [7,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation